2023
DOI: 10.1029/2022jb024150
|View full text |Cite
|
Sign up to set email alerts
|

A Microphysical Model of Rock Friction and the Brittle‐Ductile Transition Controlled by Dislocation Glide and Backstress Evolution

Abstract: Rate-and state-friction (RSF) has been used for decades to describe the frictional sliding of rocks and gouge in the laboratory (Marone, 1998;Scholz, 2002). Although it is empirical in nature, it has been applied successfully to explain phenomena in the context of both earthquake nucleation (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 123 publications
(281 reference statements)
0
5
0
Order By: Relevance
“…In this case, the compaction viscosity would control the time scale for frictional state evolution (Chen, Niemeijer & Spiers 2017; Thom et al. 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the compaction viscosity would control the time scale for frictional state evolution (Chen, Niemeijer & Spiers 2017; Thom et al. 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In either case, once sliding has ceased, viscous creep may lead to slow compaction of the gouge (or asperities) to increase contact area and harden the fault. In this case, the compaction viscosity would control the time scale for frictional state evolution (Chen, Niemeijer & Spiers 2017;Thom et al 2023).…”
Section: Implications For Natural Systemsmentioning
confidence: 99%
“…Recently, however, a series of investigations have revealed that the friction coefficient is not a constant material parameter; rather, it is dependent on a number of factors, for example, ambient temperature, stress state, moisture, damage state, friction rate, and spatio-temporal scale (Ben-David & Fineberg, 2011;Putelat et al, 2011;Scholz, 2019;Zhang & Ma, 2021;C. X. Zhao, Liu, et al, 2023;Thom et al, 2023). Particularly, within a relatively mild ambient temperature range, the friction coefficient of rocks exhibits temperature-strengthening properties (Hu & Sun, 2020;L.…”
Section: Temperature-dependent Friction Lawmentioning
confidence: 99%
“…It is noted that in the established works devoted to constitutive modeling, the friction coefficient μ * is conventionally considered constant for the sake of simplification (Molladavoodi, 2015; Qu et al., 2021; Ren et al., 2022; Zhao, Shao, & Zhu, 2018). Recently, however, a series of investigations have revealed that the friction coefficient is not a constant material parameter; rather, it is dependent on a number of factors, for example, ambient temperature, stress state, moisture, damage state, friction rate, and spatio‐temporal scale (Ben‐David & Fineberg, 2011; Putelat et al., 2011; Scholz, 2019; Zhang & Ma, 2021; C. X. Zhao, Liu, et al., 2023; Thom et al., 2023). Particularly, within a relatively mild ambient temperature range, the friction coefficient of rocks exhibits temperature‐strengthening properties (Hu & Sun, 2020; L. N. Y. Wong et al., 2020; F. B. Yang et al., 2022).…”
Section: Formulation Of a New Micro‐thermomechanical Modelmentioning
confidence: 99%
“…The underlying physics of contact asperity friction on the microscale is still a matter of debate (e.g., Aharonov & Scholz, 2018; Chen et al., 2021; Thom et al., 2023), and the frictional properties and stability of faults are expected to depend on multiple parameters, such as temperature, pressure (or normal stress and pore pressure), fault roughness, composition, and sliding rate (e.g., Blanpied et al., 1991; Han et al., 2007, 2010; Hayward & Cox, 2017; Hayward et al., 2019; He et al., 2007; Scholz, 2019; Stesky, 1978; Verberne et al., 2020; Yao et al., 2016). Among them, temperature and pressure are the two most important environmental factors affecting the frictional properties and stability of faults and have been extensively studied in many friction experiments on carbonate rocks, which are an important constituent of the Earth's crust.…”
Section: Introductionmentioning
confidence: 99%